Public Administration Strategy Of The Youth, Sports, And Tourism Office Of Way Kanan Regency In Developing Local Tourism Potential - Marwansyah; Tina Miniawati Barusman Virgawenda (Cita konsultindo, 2026)
Regional tourism development is one of the strategic instruments in regional development aimed at improving local economic growth and community welfare. Way Kanan Regency possesses considerable natural and cultural tourism potential; however, its utilization has not yet been optimal. This study aims to analyze the public administration strategy of the Youth, Sports, and Tourism Office of Way Kanan Regency in developing regional tourism based on the Attraction, Accessibility, and Amenity (3A) components. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observation, and documentation. The research informants consisted of officials from the Youth, Sports, and Tourism Office, tourism site managers, and other relevant stakeholders. Data analysis was conducted using the interactive model of Miles and Huberman. The results indicate that tourism development strategies in Way Kanan Regency have not been implemented optimally. In terms of Attraction, tourism resources have not been properly curated and managed. Accessibility remains the most significant constraint due to inadequate road infrastructure leading to tourist destinations. Meanwhile, the Amenity aspect shows limited and uneven availability of supporting tourism facilities. These conditions are influenced by weak strategic planning, budget limitations, and suboptimal inter-agency coordination. The study concludes that tourism development in Way Kanan Regency requires strengthening public administration strategies through integrated destination planning, enhanced cross-sector coordination, and sustainable community involvement to ensure effective management of the 3A components.